Production of millet and legumes in consortium systems for semiarid regions (Research, Society and Development, 2023)
The use of sustainable and economically viable production systems is extremely important. Therefore, the study seeks to understand the responses of the soil-plant system with the association of the use of mulch and the intercropping system of grasses and legumes. For this, a narrative bibliographic review was carried out. Pearl millet (Pennisetum glaucum (L.) R. Br.) is a plant with a short annual cycle and low water requirement (450-700 mm). When cultivated under mulch for forage production, its yield was high. This is because the use of soil mulch can increase water infiltration into the soil, contributing to greater water use efficiency in plants. Furthermore, this practice can increase soil microbial population and fertility. Concomitantly, the cultivation of millet intercropped with legumes such as cowpea and guan bean can contribute to a higher crop yield in semi-arid regions. The consortium between grasses and legumes, as long as they are compatible in terms of development, can lead to high benefits for the production of the system, since the biological fixation of atmospheric N can increase the production of biomass and forage quality for animal feed. Despite its numerous advantages, the use of mulch in millet cultivation and intercropping with legumes still needs further technical definitions and needs to be better studied. Especially with regard to the associated management of these two practices (mulch and consortium).